A expressão variável do futuro verbal no discurso político em três cidades baianas: Salvador, Feira de Santana e Vitória da Conquista - Almeida, Fernanda dos Santos (2015)
We analyze the realization of the future tense in the political discourse of the three largest cities of Bahia, Salvador, Feira de Santana, and Vitória da Conquista, based upon the Variacionist Sociolinguistics. Some sociolinguistic researches indicate a change in progress on the use of the future tense in Brazilian Portuguese, whereupon the standard variant, the simple future form, has been replaced for the periphrastic form (ir + infinitive). These researches show that this change has been completed in the speech and is already reaching writing. This research verify this change in progress in the political discourse, a formal textual genre with features of speech and writing. Some contexts promotes the progress of the periphrastic form, like: a) verbs with three or more syllables; b) younger age group; c) agent subject; d) less stylistic monitoring speech; e) second verbal person; f) regular verbs; g) first event in a serial (about parallelism). The results also show the superiority of the periphrasis ir ‘to go’ + infinitive; indicate the decline of simple future form; confirm that the simple present tense is used in very specific contexts; show the existence of periphrasis with gerundive forms, called “gerundismo”, in the standard speech; and indicate the final stage of process of change analyzed.